ANALISIS PENGARUH KEAHLIAN MENJUAL TENAGA PENJUAL, DAN KUALITAS PELAYANAN GLAXO SMITH KLEINE TERHADAP KINERJA TENAGA PENJUAL - Hendriyanto, Asepta (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2012)
This study aims to test the effects of salesperson selling skills and servicequality of sales person to salesperson sales performance. .The study used severalcustomer of Glaxo Smith Klein as sample. Data analyze instrument used by thewriter is SPSS 17.Data analyze result shows that the research model has wellappropriateness and all hypothesis of the study are able to be evidenced.Summary said that salesperson selling skill, and service quality are positivelyeffected to salesperson performance.Based on the result of the study, managerial implication given to thecompany is suggestion or input to management of Glaxo Smith Klein to give moreconcern at the salesperson selling skill, as it is the most dominant factor effectedto salesperson sales performance.